Let a Thousand Flowers Bloom: Transition towards Implementation of the IMIA Strategic Plan - Murray, P.; Haux, R.; Lorenzi, N. (Methods of Information in Medicine, 2007)
Objective: IMIA, the International Medical Informatics Association, has adopted the IMIA Strategic Plan, “Towards IMIA 2015”. In order to turn the vision into reality, we invite all members of IMIA, and others with an interest in our work, to engage in activities designed to achieve the key strategic goals of the plan.Methods: IMIA members and others are invited to study the IMIA Strategic Plan, and consider developing, or contributing to, proposals that can support the implementation of one or more parts of the Strategic Plan. IMIA has allocated a proportion of reserve funds for projectssupporting the implementation of the plan, and proposals can be submitted to the Interim Vice President for Strategic Planning Implementation.Results and Conclusions: Several projects are already being undertaken to support implementation of the IMIA Strategic Plan. IMIA looks forward to its members undertaking further projects, targeted at achieving its strategic goals and making the vision a reality by 2015.
Keywords: International Medical Informatics Association; IMIA; health informatics; medical informatics; strategy